Academic Motivation and Self-Efficacy Among Pre-Service Teachers: A Correlational Study - Siti Hardiyanti Triana; Miftahuljannah Muslimin; Sitti Nur Astuti S (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2026)
Academic motivation and self-efficacy are two important psychological constructs that play a fundamental role in supporting learning success and the professional readiness of pre-service teachers. This study aimed to analyze the levels of academic motivation and self-efficacy and to examine the correlation between these two variables among pre-service teachers in Chemistry, Physics and Mathematics education programs. A quantitative approach with a correlational design was employed, involving 90 first-year students from the Faculty of Teacher Training and Education. Data were collected using validated Likert-scale questionnaires measuring academic motivation (30 items, Cronbach's α = 0.813) and self-efficacy (20 items, Cronbach's α = 0.860), both demonstrating good internal consistency. Data were analyzed using descriptive statistics and the Pearson Product-Moment correlation test, after the normality (Kolmogorov-Smirnov, p = 0.200) and linearity assumptions were confirmed. The results indicate that students' academic motivation was in the very high category (M = 86.84, SD = 7.21), while self-efficacy was in the moderate category (M = 57.68, SD = 6.15). The correlation analysis revealed a statistically significant positive relationship between academic motivation and self-efficacy (r = .484, p = .000, p < 0.01), indicating a moderate effect size. These findings suggest that, although pre-service teachers reported very high academic motivation, their self-efficacy remained at a moderate level, indicating that motivation alone may not be sufficient to build strong competence beliefs. The results imply the need for pedagogical interventions such as gradual mastery experiences, formative feedback, and strategy modeling by lecturers to strengthen self-efficacy and help translate students' motivational energy into more stable academic performance and teaching readiness, particularly within chemistry education contexts.